Key behavioural characteristics of small-business owners: A lab-in-the-field experiment in Myanmar - John Rand; Paula Castro Rodriguez; Finn Tarp; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This study investigates the role of owners' personal preferences and behaviour in determining the success of micro, small and medium-sized enterprises using a lab-in-the-field experiment with small-business owners in Myanmar. The study is a complement to a 2017 quantitative survey conducted within the project 'Towards inclusive development in Myanmar'. The lab-in-the-field experiment comprised five behavioural games: dictator, bargaining, trust, public goods, and risk-preference elicitation. It was conducted in 12 townships in 11 states and regions of Myanmar in September and October 2018. The sample comprised 397 enterprise owners, managers, and employees. This study has a twofold contribution. First, we present for the first time the behavioural profile of small-business owners in Myanmar. Second, we link the results of different behavioural games to the main participant and enterprise characteristics. Finally, we reflect on the implications for enterprise performance and for policy as it relates to micro, small and medium-sized enterprises.
Keywords: C91; D91; L25; L26; 330; entrepreneurship; risk-taking; trust; bargaining; altruism; behaviour